Odpowiedź :
a)
x = 0.(3) /×10
10x = 3
10x = 2.7 + 0.(3)
10x = 2.7 + x
9x = 2.7
x = 0.3 = 3/10
b)
x = 0.1(6) /×10
10x = 1.6(6)
10x = 1.5 + 0.1(6)
10x = 1.5 + x
9x = 1.5
x = 0.1666 ≈ 0.17 = 17/100
x = 0.(3) /×10
10x = 3
10x = 2.7 + 0.(3)
10x = 2.7 + x
9x = 2.7
x = 0.3 = 3/10
b)
x = 0.1(6) /×10
10x = 1.6(6)
10x = 1.5 + 0.1(6)
10x = 1.5 + x
9x = 1.5
x = 0.1666 ≈ 0.17 = 17/100
0.3333333=X / 10
3.3333333=10x
3+0,33333
3+x=10x
3=10x-x
3=9x/9
3/9=x
0.(3)=3/9=1/6
0.16666666=x /10
6.16666666=10x
6+0,166666
6+x=10x
6=10x-x
6=9x /9
6/9=x
0.1(6)=1/6
3.3333333=10x
3+0,33333
3+x=10x
3=10x-x
3=9x/9
3/9=x
0.(3)=3/9=1/6
0.16666666=x /10
6.16666666=10x
6+0,166666
6+x=10x
6=10x-x
6=9x /9
6/9=x
0.1(6)=1/6